2004
DOI: 10.1152/ajprenal.00122.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antidiuretic hormone resistance in the neonatal cortical collecting tubule is mediated in part by elevated phosphodiesterase activity

Abstract: Neonates cannot concentrate their urine to the same degree as adults. One of the key factors in concentrating the urine is the renal collecting duct osmotic water permeability (Pf) response to antidiuretic hormone (ADH). Neonatal cortical collecting ducts have a blunted Pf response to ADH compared with adult tubules (Pf: 119.0 +/- 12.5 vs. 260.1 +/- 29.5 microm/s, P < 0.05). We found that the phosphodiesterase activity in the neonatal collecting ducts was higher than that in the adult collecting ducts (3,970 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Therefore, it had been assumed that increased phosphodiesterase activity was not a significant factor limiting the response of the CD to AVP. Recently, Quigley et al (86) confirmed previous observations of elevated intracellular levels of phosphodiesterase in neonatal CCD. Furthermore, they were able to show that rolipram, a specific inhibitor of phosphodiesterase IV, not only decreased phosphodiesterase activity in the immature CCD to adult levels but, more significantly, abolished the blunted AVP-stimulated osmotic water permeability in isolated, microperfused immature CCD (86).…”
Section: Role Of Phosphodiesterasessupporting
confidence: 54%
“…Therefore, it had been assumed that increased phosphodiesterase activity was not a significant factor limiting the response of the CD to AVP. Recently, Quigley et al (86) confirmed previous observations of elevated intracellular levels of phosphodiesterase in neonatal CCD. Furthermore, they were able to show that rolipram, a specific inhibitor of phosphodiesterase IV, not only decreased phosphodiesterase activity in the immature CCD to adult levels but, more significantly, abolished the blunted AVP-stimulated osmotic water permeability in isolated, microperfused immature CCD (86).…”
Section: Role Of Phosphodiesterasessupporting
confidence: 54%
“…Neonatal CT water permeability did not increase in response to vasopressin to the same extent as that seen in the adult [312][313][314][315]. Studies have shown that the phosphodiesterase activity is greater in the neonatal collecting tubule [313].…”
Section: Development Of Urinary Concentration and Dilutionmentioning
confidence: 62%
“…Neonatal CT water permeability did not increase in response to vasopressin to the same extent as that seen in the adult [312][313][314][315]. Studies have shown that the phosphodiesterase activity is greater in the neonatal collecting tubule [313]. The water permeability of the neonatal collecting tubule was identical to the adult in the presence of a phosphodiesterase inhibitor demonstrating that the predominant factor limiting the action of vasopressin in the collecting tubule was the enhanced degradation of cAMP generated by vasopressin in the neonatal collecting tubule [313].…”
Section: Development Of Urinary Concentration and Dilutionmentioning
confidence: 74%
See 1 more Smart Citation
“…Evidence suggests that ␤-adrenergic signaling promotes Na excretion by facilitating a blood-lumen flux of Na ϩ , 20 whereas other studies have indicated that ␤-adrenergic signaling inhibits Na ϩ uptake in tubules by stimulating basolateral Na/K ATPase. [22][23][24] Additional renal effects of rolipram that have been reported include regulation of the osmotic permeability response to antidiuretic hormone in neonatal tubules 25 and renin release from juxtaglomerular cells. 26 Both the Dahl SS rats and SHRs are generally considered to be models of renal hypertension.…”
Section: Discussionmentioning
confidence: 99%